Auctions with Variable Supply: Uniform Price versus Discriminatory - Damian S. Damianov; Johannes Gerd Becker (ETH Zurich, CER-ETH - Center of Economic Research, 2008)
We examine an auction in which the seller determines the supply after observing the bids. We compare the uniform price and the discriminatory auction in a setting of supply uncertainty. Uncertainty is caused by the interplay of two factors: the seller's private information about marginal cost, and the seller's incentive to sell the profit-maximizing quantity given the received bids. In every symmetric mixed strategy equilibrium, bidders submit higher bids in the uniform price auction than in the discriminatory auction. In the two-bidder case this result extends to the set of rationalizable strategies. As a consequence, we find that the uniform price auction generates higher expected revenue for the seller and higher trade volume.
Keywords: D44; 330; sealed bid multi-unit auctions; variable supply auctions; discriminatory and uniform price auctions; subgame perfect equilibria; rationalizable strategies; Auktionstheorie; Theorie